Urgensi Regulasi atas Produk Artificial Intelligence Sebagai Upaya Perlindungan Hukum di Indonesia - Siregar, Namira Romaito; Saidin, Saidin; Leviza, Jelly; Andriati, Syarifah Lisa (Universitas Medan Area, 2024)
This study aims to analyze the Regulation of Legal Protection on the Utilization of Artificial Intelligence Works in the Empowerment of Intellectual Property Rights in Indonesia and analyze the Urgency of Regulation on Patent Law Problems in Indonesia as the Utilization of Artificial Intelligence Works in Comparison with Japan. This study uses normative legal methods with a comparative approach to analyze AI patent protection, utilizes literature studies, and aims to provide recommendations for regulatory development in Indonesia. The results of the study show that legal protection for AI works in Indonesia is urgent to be developed through adaptive and specific regulations. Legal ambiguity in Law No. 13 of 2016 hampers the protection of AI patents, while Japan has shown mature and comprehensive regulations. Revisions to the law in Indonesia are needed to include AI copyright and patent protection, encourage innovation, and attract investment. Learning from Japan, Indonesia can create a legal system that is conducive to the growth of AI-based technology. Responsive regulation will ensure AI is used legally and benefits society.